On the nomenclature of the palaemonid names Palaemon spinipes Desmarest, 1817, Palaemon spinipes Schenkel, 1902, and Macrobrachium wallacei Wowor & Ng, 2008 (Crustacea: Decapoda: Caridea) - Ng, P.K.L. (2014)
Zootaxa